2016
DOI: 10.1186/s12859-016-1372-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural analyses of 2015-updated drug-resistant mutations in HIV-1 protease: an implication of protease inhibitor cross-resistance

Abstract: BackgroundStrategies to control HIV for improving the quality of patient lives have been aided by the Highly Active Anti-Retroviral Therapy (HAART), which consists of a cocktail of inhibitors targeting key viral enzymes. Numerous new drugs have been developed over the past few decades but viral resistances to these drugs in the targeted viral enzymes are increasingly reported. Nonetheless the acquired mutations often reduce viral fitness and infectivity. Viral compensatory secondary-line mutations mitigate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…We found that VL increased only modestly after failure, driven mostly by low adherence and development of PI mutations. Our finding of an initial relatively large increase in VL followed by a plateau in replication after I47A development is supported by in vitro evidence [33,35]; contrary to this literature, we did not find a difference in virus that also had the V32I mutation, although numbers were small. Other PI mutations had comparatively modest effects as observed elsewhere [36], although not all studies have observed this effect [10].…”
Section: ~20% Of Patients Had Intermediate/high-level Lopinavir Resissupporting
confidence: 72%
See 1 more Smart Citation
“…We found that VL increased only modestly after failure, driven mostly by low adherence and development of PI mutations. Our finding of an initial relatively large increase in VL followed by a plateau in replication after I47A development is supported by in vitro evidence [33,35]; contrary to this literature, we did not find a difference in virus that also had the V32I mutation, although numbers were small. Other PI mutations had comparatively modest effects as observed elsewhere [36], although not all studies have observed this effect [10].…”
Section: ~20% Of Patients Had Intermediate/high-level Lopinavir Resissupporting
confidence: 72%
“…I47A was often followed by V32I, and developing I47A was associated with a lower odds of developing I54V and vice versa. This has important consequences for third-line ART, as I47A confers intermediate-level resistance to darunavir and V32I is suggested as a key mutation for high-level resistance [32,33], whereas I54V is not known to affect darunavir response [13]. We also frequently observed the V82A mutation¸ thought to improve susceptibility to darunavir [34].…”
Section: ~20% Of Patients Had Intermediate/high-level Lopinavir Resismentioning
confidence: 88%
“…Differing from RT, symmetrical allosteric communications between domains in HIV-1 integrase and protease are found [95,96], probably resulting from the homo-multimerization (Figure 2A). Mutations on the C-terminal domain (CTD, residues 220-221, 230-232, and 211-217) of integrase and at the "ears" regions of protease (residues 33-45 and 57-63, of which residues L33, E34, and M36 were reported to be resistant to several protease inhibitors [79]) have been found to affect the active sites of the two enzymes ( Figure 2B).…”
Section: Analysis Of Allosteric Communicationmentioning
confidence: 99%
“…By analysing the standard Barton502 dataset using support vector regression on informative physicochemical properties, Liou et al [17] show that an aligned row (called spline) of solventexposed hydrophobic residues actually stabilise ɑ-helices in proteins. Su et al [18] have used structural bioinformatics approaches to correlate recent clinically identified mutation in HIV-1 protease with different protease inhibitors used as drugs. Their results provide an insight into the mechanism for HIV-1 drug resistance and suggest a protease inhibitor drug may selection strategy for clinical applications.…”
Section: Protein Structural Bioinformaticsmentioning
confidence: 99%